Proposed new interior design for Thomas and Guys Academy Sdn. Bhd. at Lot 211, Seksyen 24, Jalan Empayar Off, Persiaran Sultan lbrahim KU1, 41300 Klang, Selangor Darul Ehsan / Hasliza Haidi - Haidi, Hasliza (2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student's knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design for Thomas and Guys Academy Sdn. Bhd. at Lot 211, Seksyen 24, Jalan Empayar Off, Persiaran Sultan lbrahim/KU1, 41300 Klang, Selangor Darul Ehsan. This proposed haic salon and academy is to attract people, mostly on student to educate themselves in hairstyling couses offered at Thomas and Guys Academy, at the same time to promote their product successfully as they offered, Schwarzkopf and interiors, that is truly different from other hair salon and academy range that comes mostly from Modern Exotic images. The target market for the users of this spa range product is from all age and classes that are concern about their look and appearances, not forgetting to find those who are interested in studying in hair styling couses. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Thomas and Guys Academy. Connected to that, the chosen design style for Thomas and Guys Hair salon and Academy is based on Modern Exotic design, goes all the way with the client's needs as they want the hair salon and academy have the modern look and at the same time would attract the customers with different image that they would only get in Thomas and Guys Academy. Before getting a desired design that is suitable with the client's needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and informations about other hair salon and academy that use the same system in management, as the proposed hair salon and academy. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.